Evaluation of Validity of Computer Based Test Items in NOUN - Charity Akuadi Okonkwo (West African Journal of Open and Flexible Learning, 2018)
Multiple Choice Items (MCI) are one of the most commonly used Computer Based Assessment (CBA) instrument for assessment of students in educational settings especially in Open and Distance Learning (ODL) with large class sizes. The MCI making up the assessment instruments need to be examined for quality which depends on its Difficulty Index (DIF I), Discrimination Index (DI), and Distractor Efficiency (DE) if they are to meaningfully contribute to validity of the students’ examination scores. Such quality characteristics are amenable to examination by item analysis. Hence, the objective of this study is to evaluate the quality of MCI used for CBA in the National Open University of Nigeria (NOUN) as formative assessment measures by employing expost facto research design. One foundation course in School of Education of the University was used for the study. The aim was to develop a pool of valid items by assessing the items DIF I, DI and DE and also to store, revise or discard items based on obtained results. In this cross-sectional study, 240 MCI taken in four (4) sets of CBA per semester per course in 2012 – 2014 academic years were analysed. The data was entered and analysed in MS Excel 2007. The results indicated items of “good to excellent” DIF I and “good to excellent” DI, Efficient Distractors (DE) and non-functional distractors (NFD). Also established were items with poor DI. This study emphasized the selection of quality MCI which truly assess levels of students learning and differentiate students of different abilities in correct manner in NOUN thereby contributed to improving the validity of the test items.